Utilisation of Rhododendron luteum Sweet bioactive compounds as valuable source of enzymes inhibitors, antioxidant, and anticancer agents - ŞENKARDEŞ, İSMAİL (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Ethnobotanical evidences report the use of Rhododendron luteum Sweet (Ericaceae) in traditional medicinal systems. However, R. luteum has been associated to the occurrence of 'mad honey' poisoning. In the present study, the ethyl acetate, methanol, and water extracts of R. luteum were investigated for their in vitro antioxidant, enzyme inhibition, and cytotoxic properties. The cytotoxicity of R. luteum extracts on A549 lung cancer cell line was evaluated using MTT cell viability assay. Besides, HPLC-ESI-MSn approach was employed to elucidate the secondary metabolite profiles of R. luteum in order to establish any structure-activity relationship. Methanol and water extracts of R. luteum possessed highest radical scavenging and reducing properties while the ethyl acetate extract showed highest metal chelating properties. In terms of enzyme inhibition, the methanol and ethyl acetate extracts of R. luteum, possessing epigallocatechin, were active inhibitors of cholinesterase enzymes, a-glucosidase, and tyrosinase. Water extract caused growth inhibition of A549 cells with 207.2 mu g/ml IC50 value. Though R. luteum has received little scientific attention due to the occurrence of grayanotoxins in the plant, however, data presented in this work shows promising biological activity of R. luteum and highlighted its role as a potential source of antioxidant and key enzyme inhibitors.
Keywords: Yellow azalea; Honeysuckle azalea; Enzyme inhibitory; Anticancer; PCA analysis; IN-VITRO; FERULIC ACID; ASPHODELINE-ANATOLICA; EXTRACTION TECHNIQUES; ALZHEIMERS-DISEASE; CAFFEIC ACID; BUTYRYLCHOLINESTERASE; ACETYLCHOLINESTERASE; FLAVONOL; MSN